Entrepreneurial Management Coastal Muslim In The Village Bongo Gorontalo - Rahmat, Abdul (IKONOMIKA, 2017)
The aim of this research activities to proving the entrepreneurial management of the coastal Muslim community in the village of Bongo. Experimental design used in this research is quasi experiment with the design of "The One-group pre-test - Post-test Design". The results showed that the model of functional skills for women of fishermen in the village of Bongo district of Gorontalo, can be seen from several aspects, namely: (1) The control / understanding of learners (female fisherman in the village of Bongo) of the learning materials functional skills wives of the fishermen in the form of entrepreneurship, practice makes kolombengi taste of fish, practice makes fish nuggets and practice makes sticks corn fish. (2) understanding wives of the fishermen village of Bongo towards community empowerment programs and Improved skills of students in the field of entrepreneurship, especially in terms of business development and business administration, and (3 ) the ability of learners work together in a business group that can produce a product with the criteria and processes in place.